The The influence of Whistleblowing and Internal Control Systems on Fraud prevention in Village Fund Management in Kawangkoan Barat District Minahasa Regency - Grazia, Lorenza; Morasa, Jenny; Mawikere, Lidia (Universitas Sam Ratulangi, 2024)
Village fund management is a critical aspect of rural governance that is susceptible to fraudulent activities. To mitigate this risk, robuts whistleblowing mechanisms and effective internal control systems are essential. This quantitative study examines the empirical relationship between whistleblowing systems and internal control systems on fraud prevention in village fund management within West Kawangkoan District, Minahasa Regency. Primary data was collected through questionnaires distributed to 40 respondents, including village heads, secretaries, treasurers and village councils from 10 villages. Employing purposive sampling, the findings indicate that both whistleblowing and internal control systems exert a significant influence on preventing, fraud in village fund management. Keywords : Whistleblowing, Internal Control Systems, Fraud Prevention